A vascular piece in the puzzle of adipose tissue dysfunction: mechanisms and consequences. (February 2014) - Rodrigues, Tiago; Matafome, Paulo; Seiça, Raquel
Abstract In the last years, several studies unravelled many aspects of adipose tissue pathophysiology in metabolic diseases. Some studies suggested hypoxia as one of such aspects, despite the exact mechanisms and pathophysiological significance is still partially unknown. Adipose tissue was shown to be hypoxic in obesity, mainly resulting from adipocyte hypertrophy, leading to increased activation of inflammatory pathways. In animal and cell models, hypoxia-induced inflammation was shown to lead to endocrine alterations and dysmetabolism. However, recent evidences suggest that instead of a simple low oxygenation theory, adipose tissue microvasculature may be regulated by a series of factors, including vasoactive factors like angiotensin II, angiogenesis and glycation, among others. This review summarizes the current knowledge about the role of these factors in the regulation of adipose tissue irrigation and the functional consequences of adipose tissue microvascular dysfunction.